Comparison of the marginal accuracy of metal copings fabricated by 3D-printed resin and milled polymethyl methacrylate - An in vitro study - Ojasvini Arora; Nabeel Ahmed; Subhabrata Maiti (Wolters Kluwer Medknow Publications, 2022)
Computer-aided design/computer-aided manufacturing (CAD/CAM) systems have gained popularity over the traditional laboratory procedures in dentistry. In the conventional metal casting technique by burnout of a pattern, instead of using a wax pattern (which has several disadvantages), milled polymethyl methacrylate (PMMA) and 3D-printed resin patterns can also be used. The objective of the study was to assess and compare the marginal accuracy of single-crown cobalt-chromium (Co-Cr) metal copings fabricated using milled PMMA and 3D-printed resin patterns. Digital designing was done for metal coping on a prepared typodont mandibular molar using 3Shape Dental Design software. Standard Tessellation Language document of CAD design was used to fabricate 3D-printed resin patterns (Sprintray 3D printer) and milled PMMA patterns (CAD/CAM milling machine CoriTEC). A total of ten Co-Cr copings were casted, of which five belonged to Group A: 3D-printed resin and the other five to Group B: milled PMMA. The copings were assessed for marginal fit at eight different points using a stereomicroscope. Statistical analysis was done using an independent t-test. The t-test revealed a significant difference between the mean marginal gap values of the two groups, with the marginal gap values for the 3D-printed resin group (82.21 ± 15.26 μm) being lesser than that of the milled PMMA group (106.75 ± 12.76 μm). The marginal accuracy of copings fabricated using 3D-printed resin patterns was superior to that of copings fabricated from milled PMMA patterns.